Correction: Coupled effects of oil spill and hurricane on saltmarsh terrestrial arthropods. - Wokil Bam; Linda M Hooper-Bui; Rachel M Strecker; Puspa L Adhikari; Edward B Overton (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0194941.].